Gestational protein restriction alters the RANKL/OPG system in the dental germ of offsprings - Bruno Calsa; Beatriz Calloni Masiero; Marcelo Augusto Marretto Esquisatto; Rosana Catisti; Milton Santamaria, Jr (Elsevier, 2020)
Objective: Evaluate the dentinogenesis in the offspring of rats submitted to gestational protein restriction (GPR). Design: The offspring were evaluated at the 21st day of gestation (21 dG). Assessments were made of morphological parameters and the RANKL/OPG system - bone tissue maturation markers - in the upper incisor tooth germ. Pregnant 10-week-old female Wistar rats were divided into normal protein (NP, 17% casein, n = 5) and low protein (LP, 6% casein, n = 5) diet groups. At 21 dG, the offspring maxillae were collected for histomorphometric and immunohistochemical analyses. Results: The LP group showed decreased thickness of the dentin and odontoblast cell layers on the tooth germ. GPR led to decreased OPG expression and increased RANKL expression in the incisor germ. Conclusion: The results suggested that gestational protein restriction altered odontoblast RANKL/OPG expression and decreased dentin matrix deposition and thickness in tooth development.